Suitability of the stress severity index combined with remote-sensing data as a tool to evaluate drought resistance traits in potato - Hoelle, J.; Asch, F.; Khan, A.; Bonierbale, M. (Wiley, 2024)
Potato is a drought susceptible crop and even short drought spells reduce tuber yields notably. In an earlier study we developed a stress severity index (SSI) based on the development stage of a genotype at the onset of drought and the soil water deficit based on soil water tension. Here, we test the suitability of the SSI combined with remotely sensed data as a screening tool to select drought-tolerant potato geno-types. Normalized difference vegetation index (NDVI) and the photochemical reflec-tance index (PRI) were obtained from reflectance measurements and thermography. Temperature data from the thermography allow using the difference between leaf and air temperature (∆T) to estimate the transpirational cooling of the leaves. Via clus-ter analysis including SSI, tuber yield reduction under drought, NDVI, PRI and ther-mography, three groups were distinguished: 1. SSI < 1000 with fast decreasing NDVI, PRI and ∆T, 2. SSI 1000–2000 with almost constant NDVI and ∆T and 3. SSI > 2000 described by small changes of NDVI, PRI and temperature deficit. For SSI < 1000, ∆T, PRI and NDVI showed to be good indicators of genotypic performance under drought. Potential strategies for drought resistance in potato detectable through remote sens-ing are discussed.